The gospel according to James and other plays - Smith, Charles, 1955- (Ohio University Press, 2012)
This collection of five award-winning plays by Charles Smith includes Jelly Belly, Free Man of Color, Pudd'nhead Wilson, Knock Me a Kiss, and The Gospel According to James. Powerful, provocative, and entertaining, these plays have been produced by professional theater companies across the country and abroad. Four of the plays are based on historical people and events, from W.E.B. Du Bois and Countee Cullen to the Harlem Renaissance. Accurate in the way they capture the political and cultural milieu of their historical settings, and courageous in the way they grapple with difficult questions, such as race, education, religion, and social class, these plays jump off the page as powerfully as they come to life on the stage.